N-Heterocyclic Carbene-Catalyzed Cross-Coupling of Aldehydes with Arylsulfonyl Indoles - Li, Yi; Shi, Fu-Qiang; He, Qing-Li; You, Shu-Li (Organic letters, 2009)
3-(1-Arylsulfonylalkyl)indoles as electrophiles in the N-heterocyclic carbene-catalyzed umpolung reaction of aldehydes were realized for the first time. This intermolecular Stetter-type reaction features the commercially available catalyst and mild reaction conditions, providing α-(3-indolyl) ketone derivatives in high yields for a wide range of substrates.